2021
DOI: 10.35946/arcr.v41.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain-Midbrain Circuits and Peptides Involved in Hyperalgesia After Chronic Alcohol Exposure

Abstract: People living with pain report drinking alcohol to relieve pain. Acute alcohol use reduces pain, and chronic alcohol use facilitates the emergence or exaggeration of pain. Recently, funding agencies and neuroscientists involved in basic research have turned their attention to understanding the neurobiological mechanisms that underlie pain-alcohol interactions, with a focus on circuit and molecular mediators of alcohol-induced changes in pain-related behavior. This review briefly discusses some examples of work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The number of 5-HT neurons was reduced in the DRN and accompanied by a reduction in 5-HT expression in the thalamus, ACC and amygdala. These regions were selected because they mediate descending modulation of pain and receive 5-HT input from the DRN (Ab Aziz and Ahmad, 2006;Chao et al, 2021;Duan et al, 2021;Gandhi et al, 2021;Gilpin et al, 2021;Heijmans et al, n.d.;Juarez-Salinas et al, 2019;Li et al, 2019;Price, 2000;Zargarani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The number of 5-HT neurons was reduced in the DRN and accompanied by a reduction in 5-HT expression in the thalamus, ACC and amygdala. These regions were selected because they mediate descending modulation of pain and receive 5-HT input from the DRN (Ab Aziz and Ahmad, 2006;Chao et al, 2021;Duan et al, 2021;Gandhi et al, 2021;Gilpin et al, 2021;Heijmans et al, n.d.;Juarez-Salinas et al, 2019;Li et al, 2019;Price, 2000;Zargarani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The CeA distributes GABAergic neurons to these PAG neurons to inhibit the perception of pain, but in rats experiencing withdrawal in an alcohol vapor model of alcohol dependence the inhibitory CeA signals were weakened thereby facilitating nociception signals and likely leading to increased nociceptive-pain (i.e., hyperalgesia) [ 89 ]. Recent work also implicates changes in dopamine-, melanocortin- and corticotropin-releasing factor signaling in the reciprocal relationship between the midbrain and CeA that may be moderated by sex and age [ 90 ].…”
Section: Supraspinal Structures Involved In Affective-motivational As...mentioning
confidence: 99%
“…For example, pain-free patients may develop a new heightened sensitivity to painful stimuli when they undergo withdrawal from alcohol after prolonged use (Egli et al, 2012, Jochum et al, 2010. This effect has been well documented in preclinical studies where alcohol withdrawal-induced hyperalgesia is extensively reported in rodents (Alongkronrusmee et al, 2016;Dina et al, 2006;Fu et al, 2021;Gatch, 1999;Gilpin et al, 2021;Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 97%